2022
DOI: 10.3390/brainsci12030402
|View full text |Cite
|
Sign up to set email alerts
|

Brain Connectivity and Graph Theory Analysis in Alzheimer’s and Parkinson’s Disease: The Contribution of Electrophysiological Techniques

Abstract: In recent years, applications of the network science to electrophysiological data have increased as electrophysiological techniques are not only relatively low cost, largely available on the territory and non-invasive, but also potential tools for large population screening. One of the emergent methods for the study of functional connectivity in electrophysiological recordings is graph theory: it allows to describe the brain through a mathematic model, the graph, and provides a simple representation of a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…It would be interesting to parallel such computational studies running the proposed MCLRL on experimental data to verify the model predictions. A recent review [32] covered the implication of graph changes in Parkinson's and Alzheimer's diseases, which are both characterized by a progressive weakening of network connectivity. Other works addressed the study of bipolar/unipolar depression [33] and cognitive aging [34].…”
Section: Data Availability Statementmentioning
confidence: 99%
“…It would be interesting to parallel such computational studies running the proposed MCLRL on experimental data to verify the model predictions. A recent review [32] covered the implication of graph changes in Parkinson's and Alzheimer's diseases, which are both characterized by a progressive weakening of network connectivity. Other works addressed the study of bipolar/unipolar depression [33] and cognitive aging [34].…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Various electrophysiological techniques, such as positron emission tomography, magnetic resonance imaging, and electroencephalography (EEG), have been widely used to measure neuronal activity [ 9 , 10 , 11 , 12 ]. Among them, EEG technology has the advantages of low cost, good portability, and strong portability [ 13 , 14 , 15 , 16 ]. The electrical signals sent by the human brain through the EEG instrument are captured by placing electrodes on the scalp through EEG technology to record brain activity [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that EEG biomarkers can be used to identify early abnormalities in neuronal function before cortical tissue loss or cognitive decline. Many researchers believe that the disruption of functional connectivity may be a pathological characteristic of neurodegenerative diseases [ 14 ]. Several studies used coherence as a method of functional connectivity and found a significant reduction in α-band coherence in AD patients [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%